"It's a lot of pain you've got to hide": a qualitative study of the journey of fathers facing traumatic pregnancy and childbirth - A. Kothari; G. Bruxner; L. Callaway; J. M. Dulhunty (BMC, 2022)
Abstract Background This study aims to explore the emotional and behavioural responses and coping strategies of fathers or expectant fathers who faced a significant traumatic event during a partner's pregnancy, labour, or the postpartum period. Methods This prospective qualitative study of 24 fathers was conducted at a public teaching hospital in Brisbane, Australia. 'Traumatic pregnancy' was defined as a pregnancy complicated by life-threatening or severe risk to the mother and the fetus, termination of pregnancy, intrauterine fetal death or stillbirth. Semi-structured interviews of participants were conducted 3-4 months after the traumatic event. An initial qualitative analysis with automatic coding was performed using Leximancer and later followed by a six-phase manual thematic analysis. Results A pregnancy-related traumatic event had significant mental and physical impacts on fathers. Participants' reactions and coping strategies were varied and influenced by their background history, pre-existing vulnerabilities, and the gap between expectation and reality. Most fathers described a fluctuating state between their needs 'not being met' and 'being met'. These needs were conceptualised using Maslow's hierarchy and Calman's gap theory to construct a composite thematic model to depict the universal requirements of men facing a traumatic pregnancy or childbirth. Conclusions A greater understanding of the needs of men and gaps in their care is urgently needed. A targeted effort is required to make maternity services father-inclusive. This approach may assist in preventing long term consequences on fathers, partners, and their children.